The unique role of dietary L-arginine in the acceleration of peritoneal macrophage sensitivity to bacterial endotoxin - Pekarova, Michaela; Kubala, Lukas; Martiskova, Hana; Papezikova, Ivana; Kralova, Stanislava; Baldus, Stephan; Klinke, Anna; Kuchta, Radoslav; Kadlec, Jaroslav; Kuchtova, Zdenka; Kolarova, Hana; Lojek, Antonin (Immunologic research, 2013)
It is known that cells and organisms can indirectly "sense" changes in L-arginine availability via changes in the activity of various metabolic pathways. However, the mechanism(s) by which genes can be directly regulated by L-arginine in mammalian cells have not yet been elucidated. We investigated the effect of L-arginine in the in vivo model of peritoneal inflammation in mice and in vitro in RAW 264.7 macrophages. A detailed analysis of basic physiological functions and selected intracellular signaling cascades revealed that L-arginine is crucial for the acceleration of macrophage activation by bacterial lipopolysaccharide. L-arginine increased the production of reactive oxygen species, nitric oxide, release of Ca(2+), as well as inducible nitric oxide synthase expression. Interestingly, the effect of L-arginine on macrophage activation was dependent on the phosphorylation of mitogen-activated protein kinases and activity of phospholipase C. In RAW 264.7 cells, L-arginine was shown to modulate the response of macrophages toward lipopolysaccharide via the activation of G-protein-coupled receptors. According to our data, we concluded that L-arginine availability plays a key role in the initiation of intracellular signaling pathways that trigger the lipopolysaccharide-induced inflammatory responses in murine macrophages. Although macrophages are partially stimulated in the absence of extracellular L-arginine, the presence of this amino acid significantly accelerates the sensitivity of macrophages to bacterial endotoxin.
Keywords: Nitric Oxide; Cell Line; Male; extracelulárním signálem regulované MAP kinasy; peritoneální makrofágy; fosfolipasy typu C; peritonitida; signální transdukce; techniky in vitro; oxid dusnatý; mužské pohlaví; Arginine; Signal Transduction; dieta; Peritonitis; Animals; zvířata; Nitric Oxide Synthase; synthasa oxidu dusnatého; myši inbrední C57BL; Diet; myši; Extracellular Signal-Regulated MAP Kinases; buněčné linie; arginin; Type C Phospholipases; Mice, Inbred C57BL; Endotoxins; Macrophages, Peritoneal; Mice; endotoxiny; In Vitro Techniques